Some results for analyzing time-dependent frequencies of vibration signals - Tri, Tran Duong (Vietnam Journal of Mechanics, 2002)
This paper provides some results for analyzing relations between frequencies and time of vibration signals. These results have been obtained by studying the properties of wavelet transform, the spectral analysis, the Short-time Fourier transform and by using the toolboxes in the software parked MATLAB. We have created the corresponding PC programs in order to realize algorithms and for the illustration of results by exploring examples.